Brief Documentation on Selected Timber-related Plant Species with Commercial Value in Kubah National Park, Sarawak - Mohamad Fhaizal, ohamad Bukhori; Mohd Ridwan, Abd Rahman; Muhamad Ikhwan, Idris; Mohd Aminudin, Mustapha; Mohamad Razif, Othman; Noorazman, Samsudin (UNIMAS Publisher, 2019)
A comprehensive learning experience in biodiversity-related discipline is the only practical way to introduce students into the world of flora. Thus, this study was carried out at Kubah National Park as the park is known for its flora and fauna diversity to investigate plant species which are of timber-related importance. The study identified and documented seven different plant families with 12 species of timber-related usage at Kubah National Park.